Chlamydia trachomatis and oral contraceptive use: a quantitative review. Issue 4 (August 1992) - Cottingham, J; Hunter, D
Abstract : OBJECTIVES--Chlamydia trachomatis is now recognised as a major sexually transmitted disease; oral contraceptive use is rapidly increasing particularly in developing countries. There are thus important public health implications of the many reports that isolation of C trachomatis is more frequent among users of oral contraceptives. The aim of this analysis was to assess the strength and consistency of this association by summarising published studies between 1972 and 1990. DESIGN--Studies identified were grouped according to whether they were prospective or case-control studies. Data were extracted and pooled estimates of the unadjusted odds ratios were made for all studies, as well as for sub-groups defined by an index of study quality, background prevalence of C trachomatis, and the contraceptive comparison being made. LOCATION--Studies in the analysis were mainly conducted in Europe and North America; the meta-analysis was done at the Harvard School of Public Health, Boston, MA, USA. RESULTS--The pooled estimated unadjusted odds ratio for 29 case-control studies examined was 1.93 (95% CI, 1.77-2.11), indicating an almost twofold increased risk of chlamydial infection for oral contraceptive users. Neither study quality nor prevalence of C trachomatis modified this risk. When compared to the use of barrier contraceptives, however, the risk of infection for women using oral contraceptives increased to 2.91 (95% CI, 1.86-4.55). The pooled estimated protective effect of barrier methods in these studies was 0.34 (95% CI, 0.22-0.54). CONCLUSIONS--Cross-study comparisons of the relationship between oral contraceptive use and chlamydial infection are limited by the design and analysis of many component studies which did not control for confounding factors such as sexual behaviour and age. The almost twofold risk of increased chlamydial infection for oral contraceptive users, supported by the findings of two prospective studies, however, points to the importance of considering the risks and benefits of oral contraceptive use in women who are likely to be exposed to C trachomatis and other STDs. The protective effect of barrier methods emphasizes the continued need for promoting barrier methods of contraception.